Methods of planning livestock feed requirements for smallholder farmers - Assefa, Getnet; Mekonnen, Kindu; Bezabih, Melkamu; Adie, Aberra; Gebreyes, Million; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Planning feed requirements of a given livestock farm is the main and essential activity for successful and profitable husbandry. The scope of the planning could stretch from a traditional system to well organized commercial farms. Planning feed requirements for commercial livestock farms are simpler and follows established principles and guidelines. On the other hand, in traditional livestock systems, such as pastoral, agropastoral and mixed crop–livestock systems, planning feed requirements is usually a challenging task. It is generally considered as routine practice and done in a traditional way, which lacks precision and effectiveness. For example, pastoralists plan to have feed and water through moving from place to place in an annual basis. Under such circumstances, the best way of planning is through experiences, which is an established good practice through trial and error.